Damage assessment of reinforced concrete frames to ground excitations - Lim, Chee Leong (2008)
In this thesis, it has been shown that the shear strength of an RC section may increase by about 40% under EIGM loading. A damage assessment technique is proposed for response of RC frames during Phase I. This technique considers the strength-enhancement effects and reflects the possible failure mechanisms. This is applied for a structural-level model, and the results are compared with those from a material-level model. The proposed damage assessment method produces damage results similar to those from a material-level model.